Genomic variability and immunological aspects involved in response to MPXV infection - La Frazia, Simone; Garbuglia, Anna Rosa; Pauciullo, Silvia; Zulian, Verdiana; Del Porto, Paola (Frontiers in Pharmacology, 2025)
Mpox, caused by the monkeypox virus (MPXV), is a zoonotic disease that has gained global relevance after the 2022–2024 outbreak. MPXV exists in two distinct clades: clade I, associated with higher virulence and mortality, and clade II, which demonstrated increased human-to-human transmission and adaptation. Clinically, Mpox presents with rash, fever, and lymphadenopathy, with severe complications in immunocompromised individuals. Genomic surveillance has revealed rapid evolution, partly driven by APOBEC3-mediated mutagenesis, especially within immune-modulating regions. Although smallpox vaccines like MVA-BN and ACAM2000 provide cross-protection against Mpox, the MVA-BN vaccine showed a more favourable safety profile, but variable effectiveness compared to replicating vaccines. Antiviral agents such as tecovirimat and cidofovir have been used off-label, but emerging resistance and limited clinical efficacy highlight an urgent need for MPXV-specific therapeutics. The current epidemiological scenario emphasizes the importance of novel antiviral development and optimized prophylactic strategies to improve clinical outcomes and global preparedness. This review aims to provide a comprehensive overview of the molecular biology, clinical features, the current drugs used to treat Mpox infection and the vaccines used to prevent the infection. It also discussing the limitations of these therapeutic tools and the improvements needed to enhance their efficacy.